2020
DOI: 10.1038/s41598-020-71898-8
|View full text |Cite
|
Sign up to set email alerts
|

Predicting county-scale maize yields with publicly available data

Abstract: Maize (corn) is the dominant grain grown in the world. Total maize production in 2018 equaled 1.12 billion tons. Maize is used primarily as an animal feed in the production of eggs, dairy, pork and chicken. The US produces 32% of the world’s maize followed by China at 22% and Brazil at 9% (https://apps.fas.usda.gov/psdonline/app/index.html#/app/home). Accurate national-scale corn yield prediction critically impacts mercantile markets through providing essential information about expected production prior to ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…In the model forecasting the yield at the end of May, one of the important factors influencing the rapeseed's proper growth and development was the average air temperature in the period from 1 to 31 May. Jiang et al [79], when forecasting the yield of maize for ten states in the United States, identified the ten best input variables, including minimum, maximum, and average temperature.…”
Section: Primary Factorsmentioning
confidence: 99%
“…In the model forecasting the yield at the end of May, one of the important factors influencing the rapeseed's proper growth and development was the average air temperature in the period from 1 to 31 May. Jiang et al [79], when forecasting the yield of maize for ten states in the United States, identified the ten best input variables, including minimum, maximum, and average temperature.…”
Section: Primary Factorsmentioning
confidence: 99%
“…One of the avenues to yield prediction is through the fusion of high dimensional phenotypic trait data using machine learning (ML) approaches to provide plant breeders the tools to do in-season seed yield (SY) prediction [7], and fusing ML and optimization techniques to identify a suite of in-season phenotypic traits collected from multiple sensors that decrease the dependence on resource-intensive end-season phenotyping in breeding programs [8]. Other avenues have been through integrating weather and genetic information in conjunction with deep time series attention models for crop SY prediction [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these models also integrate remotely sensed satellite information such as soil moisture or leaf area index [12][13][14][15]. A strong research bias has been toward modeled corn yields versus other crops with any of these methods [16][17][18][19][20]. Predictions from any of these models can be good, but they suffer from complexity in an operational setting because many input datasets and assumptions must be managed.…”
Section: Introductionmentioning
confidence: 99%